Aldose reductase inhibition alleviates hyperglycemic effects on human retinal pigment epithelial cells. (5th June 2015) - Chang, Kun-Che; Snow, Anson; LaBarbera, Daniel V.; Petrash, J. Mark
Abstract: Chronic hyperglycemia is an important risk factor involved in the onset and progression of diabetic retinopathy (DR). Among other effectors, aldose reductase (AR) has been linked to the pathogenesis of this degenerative disease. The purpose of this study was to investigate whether the novel AR inhibitor, beta-glucogallin (BGG), can offer protection against various hyperglycemia-induced abnormalities in human adult retinal pigment epithelial (ARPE-19) cells. AR is an enzyme that contributes to cellular stress by production of reactive oxygen species (ROS) under high glucose conditions. A marked decrease in cell viability (from 100% to 78%) following long-term exposure (4 days) of RPE cells to high glucose (HG) was largely prevented by siRNA-mediated knockdown of AR gene expression (from 79% to 97%) or inhibition using sorbinil (from 66% to 86%). In HG, BGG decreased sorbitol accumulation (44%), ROS production (27%) as well as ER stress (22%). Additionally, we demonstrated that BGG prevented loss of mitochondrial membrane potential (MMP) under HG exposure. We also showed that AR inhibitor pretreatment reduced retinal microglia-induced apoptosis in APRE-19 cells. These results suggest that BGG may be useful as a therapeutic agent against retinal degeneration in the diabetic eye by preventing RPE cell death.